Why have Voluntary Time-of-Use Tariffs Fallen Short in the Residential Sector? - Murali,Karthik; Choi,Dong Gu; Lim,Michael Kim; Thomas,Valerie (Production and Operations Management, 2020)
We investigate the causes behind the underwhelming adoption of voluntary Time-of-Use (TOU) tariffs in the residential electricity market. TOU tariffs are deployed by utilities to better match electricity generation capacity with market demand by giving consumers price incentives to reduce their consumption when electricity demand is at its peak. However, consumers in residential electricity markets are heterogeneous in their consumption preferences. Hence, utilities face a trade-off when deploying voluntary TOU tariffs---to provide aggressive price incentives that will only appeal to consumers with flatter profiles or milder incentives to appeal to a larger proportion of the market. Using a game-theoretic model, we identify the key factors that determine the viability of voluntary TOU tariff deployment. On the supply side, the gap between wholesale prices in the peak and off-peak periods determines how much the utility stands to benefit by inducing demand response. On the demand side, heterogeneity within target consumer sets determines how much demand response the utility can induce with a certain price incentive. We show that misaligned incentives between utilities and regulators lead to underwhelming TOU tariff adoption compared to the socially desirable level, and that this under-adoption is worse when consumption preferences are uniformly distributed. We also evaluate the degree of cross-subsidization across tariff structures to identify their implications for equity among the different consumer types, and find that low levels of voluntary TOU adoption are less equitable than the default tariffs.
Keywords: Supply Chain